LncRNA PVT1 Knockdown Ameliorates Myocardial Ischemia Reperfusion Damage via Suppressing Gasdermin D-Mediated Pyroptosis in Cardiomyocytes - Li, Cuizhi; Song, Huafeng; Chen, Chunlin; Chen, Shaoxian; Zhang, Qiyu; Liu, Dehui; Li, Jinglong; Dong, Haojian; Wu, Yueheng; Liu, Youbin (Frontiers in Cardiovascular Medicine, 2021)
Objective: Myocardial ischemia reperfusion (I/R) damage is a life-threatening vascular emergency after myocardial infarction. Here, we observed the cardioprotective effect of long noncoding RNA (lncRNA) PVT1 knockdown against myocardial I/R damage. Methods: This study constructed a myocardial I/R-induced mouse model and a hypoxia/reoxygenation (H/R)-treated H9C2 cells. PVT1 expression was examined via RT-qPCR. After silencing PVT1 via shRNA against PVT1, H&E and Masson staining was performed to observe myocardial I/R damage. Indicators of myocardial injury including cTnI, LDH, BNP and CK-MB were examined by ELISA. Inflammatory factors (TNF-α, IL-1β and IL-6), Gasdermin D (GSDMD) and Caspase1 were detected via RT-qPCR, western blot, immunohistochemistry, or immunofluorescence. Furthermore, CCK-8 and flow cytometry were presented for detecting cell viability and apoptosis. Results: LncRNA PVT1 was markedly up-regulated in myocardial I/R tissue specimens as well as H/R-induced H9C2 cells. Silencing PVT1 significantly lowered serum levels of cTnI, LDH, BNP and CK-MB in myocardial I/R mice. H&E and Masson staining showed that silencing PVT1 alleviated myocardial I/R injury. PVT1 knockdown significantly lowered the production and release of inflammatory factors as well as inhibited the expression of GSDMD-N and Caspase1 in myocardial I/R tissue specimens as well as H/R-induced H9C2 cells. Moreover, silencing PVT1 facilitated cell viability and induced apoptosis of H/R-treated H9C2 cells. Conclusion: Our findings demonstrated that silencing PVT1 could alleviate myocardial I/R damage through suppressing GSDMD-mediated pyroptosis in vivo and in vitro. Thus, PVT1 knockdown may offer an alternative therapeutic strategy against myocardial I/R damage.